1996
DOI: 10.1080/009841096161366
|View full text |Cite
|
Sign up to set email alerts
|

Catalase and Superoxide Dismutase Activities as Biomarkers of Oxidative Stress in Workers Exposed to Mercury Vapors

Abstract: For this article we investigated the role of three blood antioxidant enzyme activities and total antioxidant status (TAS) as biological markers of oxidative stress in workers exposed to mercury (Hg(o)) vapors. Twenty-two female workers took part in the study. The examination included a questionnaire on age, educational level, occupational history, actual health status, previous accidents and diseases, smoking and dietary habits, and alcohol consumption. Blood and urine sampling for biological analyses complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…1991). Recently, Perrin-Nadif et al (1996) reported altered blood SOD and catalase in Hg-exposed workers and suggested these enzymes as biomarkers of oxidative stress . Although our investigation has shown dosedependent changes in RBC antioxidant enzymes, further work correlating enzymatic changes with blood metal levels particularly in human subjects exposed to heavy metals is needed in order to validate the possible use of these parameters for an early diagnosis and toxicity evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…1991). Recently, Perrin-Nadif et al (1996) reported altered blood SOD and catalase in Hg-exposed workers and suggested these enzymes as biomarkers of oxidative stress . Although our investigation has shown dosedependent changes in RBC antioxidant enzymes, further work correlating enzymatic changes with blood metal levels particularly in human subjects exposed to heavy metals is needed in order to validate the possible use of these parameters for an early diagnosis and toxicity evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we assessed oxidative stress in workers exposed to oxidants by measuring the blood antioxidant enzyme activities and total plasma antioxidant concentration mentioned above. Recently, we found that erythrocyte catalase and Cu ϩϩ / Zn ϩϩ SOD activities were increased in workers with higher creatinine-corrected concentration of mercury (Hg) in urine when compared with workers with lower creatininecorrected concentration of Hg in urine [Perrin-Nadif et al, 1996b]. Moreover, catalase activity was positively correlated with the urinary creatinine-corrected concentration of Hg.…”
Section: Discussionmentioning
confidence: 98%
“…As ROS have very short half-lives [Pryor, 1986] and cannot be directly measured in epidemiological studies, we measured total plasma antioxidant concentration and blood antioxidant enzyme activities to assess the effects of chronic occupational exposure to oxidants in humans. Recently, we found that erythrocyte catalase and Cu ϩϩ /Zn ϩϩ SOD activities could be considered markers of oxidative stress in workers exposed to mercury vapors [Perrin-Nadif et al, 1996b]. Although antioxidant enzymes are closely related to carcinogenesis [Sun, 1990], the relationship between occupational exposure to PAHs and oxidative stress has not been sufficiently investigated in healthy exposed workers.…”
Section: Introductionmentioning
confidence: 99%
“…36 Various endogenous adaptive responses with the endogenous antioxidant enzymes (CAT, GSH, and SOD) come into play to counteract the damage caused by ROS. 37,38 In pathologic conditions of altered redox balance, these enzymes are consumed to neutralize free radicals; therefore, measurement of the endogenous antioxidant enzymes have been performed to assess the amount of oxidative stress. The activity of the CAT was significantly raised, whereas the GSH and SOD was significantly reduced in cardiac tissue of the DIC alone and/or in combination with the DOX-treated animals compared with the control (P , 0.05 and P , 0.001) and the toxic control (P , 0.001) animals, respectively.…”
Section: Discussionmentioning
confidence: 99%